Introduction and establishment of pissodes castaneus (Coleoptera: Curculionidae) in the Andean Patagonia of Argentina - Pereyra, Vanina Antonella (2015)
The pine weevils that occur in plantations of Pinus spp. in Andean Patagonia of Argentina belong to the species Pissodes castaneus (De Geer), a Eurasian endemic species, according to the identification based on molecular and morphological characters. Sequences of the mitochondrial Cytochrome oxidase subunit I and nuclear genes (28 S rDNA and ITS2) were obtained for individuals of 13 afforestations, covering the entire distribution area of the established populations in the Andean Patagonia of Argentina. Sequence comparison with representative species of the genus (European, North American, and Chinese species) shows that Patagonian specimens are conspecific to those of P. castaneus sequenced from Europe. Phylogenetic analyses indicate that all terminals from Patagonia form a monophyletic unit without evident subclades, eliminating the possibility of existence of more than one species of Pissodes Germar in this area, including cryptic ones. Moreover, the very low genetic divergence between the Patagonian populations suggests that it is plausible that P. castaneus was introduced into Patagonia from just one location. Mitochondrial DNA analysis shows that Patagonian terminals group together with a French haplotype and are clearly separated from other P. castaneus individuals represented in our sample, and reveal that established populations in Andean Patagonia originated via a limited introduction.